NILAI-NILAI PENDIDIKAN AKHLAK DALAM BUKU “TUHAN, MAAF KAMI SEDANG SIBUK” KARYA AHMAD RIFA’I RIF’AN - Muhammad Solehan (Prodi PGMI IAIN Salatiga, 2009)
This study has the formulation of the problem as follows: How is biography Ahmad Rifa'I Rif'an? How are the values of moral education in the book of Tuhan, Maaf Kami Sedang Sibuk? How is the application of moral education methodology in the book? How to implement the values of moral education in the book? This research use literature study which examines in depth about the book. Source of data come from primary data and secondary data. To analyze the existing data, the author organize, select and sort to find patterns and synthesize then conclude. The method of analysis use inductive and deductive. The findings show that Ahmad Rifa'I Rif'an born in Lamongan 3 Oktiber 1987. He is a young writer and businessman Marsua Media Owner. Patterns of thought in his book include personal development, motivation, religion and business. The concept of moral education in the book of Tuhan, Maaf Kami Sedang Sibuk is a balance in the vertical relationship (Hablumminallah) as a servant of God and the horizontal relationship (hablumminannas) as individual beings and social beings to achieve the degree of piety. Implementation in moral education in schools include: a) Implementation of materials: In connection with the development dimension in the vertical and horizontal dimensions. Besides, the implementation of direct practice of the student in daily life. b) Implementation methods: as method above moral education. c) Implementation of interest: the highest goal (taqwa), general purpose (to achieve self-realization), and special purpose (vision and mission of the school).